Dinamika kinerja guru: Peran krusial supervisi pengawas, kepemimpinan kepala sekolah, dan motivasi kerja guru - Anisaunnafi’ah, Rifka; Syahri, Syahri; Purnami, Agustina Sri (Bulletin of Educational Management and Innovation, 2024)
Background: This research is motivated by the importance of teacher performance in determining the quality of education. Factors such as supervisory supervision, principal leadership, and teacher work motivation are thought to have a significant contribution to teacher performance. Method: To test this hypothesis, quantitative methods were used with multiple and partial regression approaches. Data was collected from 21 schools and analyzed to determine the extent to which each factor influences teacher performance. In addition, the data collection technique used a questionnaire. The data analysis technique used multiple linear regression and partial correlation.   Findings: The research results show that there is a significant positive influence on the contribution of supervisory supervision, principal leadership, and work motivation on teacher performance with an effective contribution of 76.8%. These findings indicate that these three factors play an important role in improving teacher performance. Therefore, efforts to improve teacher performance should be focused on improving the quality of supervisory supervision, principal leadership, and teacher work motivation.